ACCELERATING ITERATIVE ALGORITHMS FOR SYMMETRICAL LINEAR COMPLEMENTARITY-PROBLEMS - Depierro, A. R.; Lopes, J. M. (Gordon Breach Sci Publ Ltd, 1994)
We propose a method for accelerating iterative algorithms for solving symmetric linear complementarity problems. The method consists in performing a one-dimensional optimization in the direction generated by a splitting method even for non-descent directions. We give strong convergence proofs and present numerical experiments that justify using this acceleration.
Keywords: ITERATIVE ALGORITHMS; ACCELERATION; SYMMETRICAL LINEAR COMPLEMENTARITY PROBLEMS